2019
DOI: 10.1155/2019/3569018
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Outcomes among Multidrug Resistant Tuberculosis Patients in Tanzania

Abstract: Background. According to World Health Organization (WHO) the final multidrug resistant tuberculosis (MDRTB) treatment outcome is the most important direct measurement of the effectiveness of the MDRTB control program. Literature review has shown marked diversity in predictors of treatment outcomes worldwide even among the same continents. Therefore, findings could also be different in Tanzanian context, where the success rate is still lower than the WHO recommendation. This study sought to determine the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
28
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 30 publications
11
28
3
Order By: Relevance
“…Patients who have a history of second-line anti-TB drug resistance were more likely to have poor treatment outcomes. The nding of this study is in line with studies done in India, Pakistan, and Tanzania [14,15,16].…”
Section: Discussionsupporting
confidence: 89%
“…Patients who have a history of second-line anti-TB drug resistance were more likely to have poor treatment outcomes. The nding of this study is in line with studies done in India, Pakistan, and Tanzania [14,15,16].…”
Section: Discussionsupporting
confidence: 89%
“…The study participants for ten of the included studies [ 22 , 26 – 34 ] were mixed-age patients; for 7 of the included studies [ 23 25 , 35 38 ] were adults; for one of the included study [ 39 ] were adolescents and adults, and for the rest one of the included study [ 40 ] were children. Eleven (n = 11) of the included studies were from southern region of SSA [ 23 , 24 , 26 , 27 , 32 , 34 – 37 , 39 , 40 ], while 6 [ 25 , 28 31 , 33 ] and 2 [ 22 , 38 ] of them were from eastern and western regions, respectively ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to a study in Tanzania that found that patients with cavities on chest X ray had better treatment outcomes but dissimilar to a study in Egypt where patients with advanced disease on chest X ray had worse outcomes. A different study in Malaysia revealed no significant associations between patients with chest x ray findings and treatment outcomes [30,28,27]. This finding could be as result of the different variations in chest X ray interpretation among radiologists and radiographers.…”
Section: Discussionmentioning
confidence: 98%